The Influence of Institutional Ownership, Corporate Risk, Board of Commissioners Independence, Company Size and Profitability on Audit Fees - Viyati, Gusnel; Nasrah, Hidayati; Suryadi, Nanda (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to determine This study aims to determine the the influence of Institutional Ownership, Corporate Risk, Board of Commissioners Independence, Company Size, and Profitability on Audit Fees in BUMN listed on the IDX for the 2021-2022 period. The sampling technique used wan purposive sampling with a total sample of 27 sample with a 2-years research period. The data analysis method uses panel data regression analysis through the Eviews 12 application. The result of this study indicates the variable of institusional ownership, independence of the board of commissioners and profitability does not have an effect on audit fees. While, firm risk, company size has an effect on audit fees.